2015
DOI: 10.1002/nem.1898
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of topological inconsistency attacks in RPL‐based low‐power lossy networks

Abstract: SUMMARYRPL is a routing protocol for low-power and lossy networks. A malicious node can manipulate header options used by RPL to create topological inconsistencies, thereby causing denial of service attacks, reducing channel availability, increased control message overhead, and higher energy consumption at the targeted node and its neighborhood. RPL overcomes these topological inconsistencies via a fixed threshold, upon reaching which all subsequent packets with erroneous header options are ignored. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 16 publications
0
55
0
Order By: Relevance
“…Dvir et al suggested an authentication scheme named VeRA to detect two routing attacks, ie, version number and decreased rank. A dynamic threshold–based defense mechanism is proposed by Mayzaud et al to mitigate DODAG inconsistency attacks. Ghaleb et al studied the impact of DAO falsification attack and proposed a defense mechanism named SecRPL to mitigate DAO falsification attack.…”
Section: Related Workmentioning
confidence: 99%
“…Dvir et al suggested an authentication scheme named VeRA to detect two routing attacks, ie, version number and decreased rank. A dynamic threshold–based defense mechanism is proposed by Mayzaud et al to mitigate DODAG inconsistency attacks. Ghaleb et al studied the impact of DAO falsification attack and proposed a defense mechanism named SecRPL to mitigate DAO falsification attack.…”
Section: Related Workmentioning
confidence: 99%
“…As a result the targeted node will discard the packet and reset the trickle timer; hence, the control messages will be sent more frequently which will waste energy and increase delay. In [57], authors proposed to limit the rate of tickle timer resets to 20, while in [58] and [59] two methods, adaptive threshold and dynamic approach, were used. On the other side, in the case of rank attack an adversary can attract the large traffic by advertising false rank value, so non-optimal routes might be established.…”
Section: B Security and Attacks In Rplmentioning
confidence: 99%
“…Separate keys for network segments [48] PS The solution was not implemented/simulated yet; Merkel trees authentication [54] PS Node uses a key to encrypt its messages; High jitter and E2E delay until tree has been established; Graph theoretic approach [55] PS Cryptographic techniques based on local broadcast keys; Low overhead, no synchronization needed; Sybil attack, Clone ID Distributed hash tables (DHT) to store the graphical location of nodes [48], [56] PS Problem in how to securely verify the node location; Might not scale well with large networks; DAG/DAO inconsistency attack Limit the rate of tickle timer resets [57] PS Threshold value is fixed, no network or node characteristics are taken into account; Adaptive threshold [58] PS Takes into account the network characteristics; Dynamic approach [59] PS Improved version as node specific parameters are used; Rank attack VeRa [60] PS Authentication mechanism based on hash operations; Low time overhead, but still vulnerable to rank attacks by forgery and replay; TRAIL [61] PS Improvement of VeRa, requires almost no cryptography, but shows dependency on network sizes; choose to selectively forward data or drop all received packets. In both scenarios the network operation would be disturbed.…”
Section: Psmentioning
confidence: 99%
“…Another mitigation technique for DODAG inconsistency attacks was proposed by Mayzaud et al [33] in 2015. It is an improved version of the mitigation technique proposed in Sehgal's work [49].…”
Section: Mitigation Systems and Protocol Security Solutions For Intermentioning
confidence: 99%